Calvin Cutter biography - Cutter, Calvin, 1807-1873?
Account of Cutter's abolitionist activities in prewar Kansas, friendship with John Brown, and Civil War service with the 21st Massachusetts in Kentucky, North Carolina, and Virginia.
Handwritten transcript.
Army officer and surgeon.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brown, John, -- 1800-1859.; United States. -- Army. -- Massachusetts Infantry Regiment, 21st (1861-1864); Antislavery movements -- Kansas; Kansas -- History -- 1854-1861.; Kentucky -- History -- Civil War, 1861-1865.; Massachusetts -- History -- Civil War, 1861-1865.; North Carolina -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Army officers; Surgeons